Bush's brain - Moore, James (Wiley, 2003)
The book is the first in-depth examination of Rove's remarkable political journey, as well as a straightforward narrative of the key role he has played in George W. Bush's rise to the top. Equal parts biography and history of late twentieth-century politics, this fascinating book pieces together the puzzle of Rove's extraordinary political life through personal interviews with Rove himself as well as revealing stories from friends and foes alike.